Analysis and Research on Oil Injection Lubrication of Variable Tooth Thickness Gear Based on CFD Method - Huicheng Zhang; Yongping Liu; Qi Chen (Applied Sciences)
Variable tooth thickness gears have significant effects on the characteristics of the flow field inside the gearbox and the lubrication efficiency under high-speed operating conditions due to their complex parameters, such as tooth profile, cone angle, rotational speed, and oil injection speed. To investigate the impact mechanism of oil injection velocity on the working flow field of high-speed variable tooth thickness gears under varying parameters, this paper establishes an oil injection lubrication model under high rotational speeds of variable tooth thickness gears, based on computational fluid dynamics (CFD) methods and the Volume of Fluid (VOF) model, combined with the dynamic mesh technique. This paper analyzes the lubrication issues at the initial oil injection moment of involute variable tooth thickness gears. By computing the lubricant distribution state at 0.1 s after the oil injection onset based on the stabilized flow field under no-oil-injection condition, discussions are conducted on the single-phase and two-phase flow fields within the gear casing at different cone angles and rotational speeds separately examining the flow states near the oil nozzle and the distribution patterns of lubricant at the meshing portions. The results indicate that, without oil injection, the pressure near the oil nozzle gradually increases with an increase in rotational speed and decreases with an increase in cone angle; at the initial oil injection moment, the lubricant volume fraction at the gear meshing portions gradually increases with an increase in rotational speed and rises with an increase in cone angle.